1985
DOI: 10.1152/ajprenal.1985.248.2.f183
|View full text |Cite
|
Sign up to set email alerts
|

Response of isolated renal arterioles to acetylcholine, dopamine, and bradykinin

Abstract: The effect of acetylcholine (ACh), dopamine (DA), and bradykinin (BK) on vascular tone was examined in interlobular arteries and superficial afferent and efferent arterioles isolated from rabbit kidney. A single microvessel was dissected and cannulated, and lumen diameter was measured at a fixed intraluminal pressure. ACh caused a dose-dependent relaxation of norepinephrine-induced tone in all three vessel types. Significant relaxation (10-20%) was observed with 10(-8) M ACh and higher concentrations caused co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
38
3

Year Published

1989
1989
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 0 publications
10
38
3
Order By: Relevance
“…This may indicate that the renal microvasculature downstream from the main renal artery produces little EDRF in response to acetylcholine. In contrast, results from both the present study and that by Edwards 18 have demonstrated that acetylcholine dilates isolated afferent arterioles preconstricted by either endothelin or norepinephrine, strongly suggesting that renal microvasculature can produce EDRF.…”
Section: Discussioncontrasting
confidence: 99%
“…This may indicate that the renal microvasculature downstream from the main renal artery produces little EDRF in response to acetylcholine. In contrast, results from both the present study and that by Edwards 18 have demonstrated that acetylcholine dilates isolated afferent arterioles preconstricted by either endothelin or norepinephrine, strongly suggesting that renal microvasculature can produce EDRF.…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, these studies provide evidence that prostaglandins may play no role in the renal vasodilator actions of PAF. We (23,32) and others (33) have demonstrated that acetylcholine dilates isolated afferent arterioles preconstricted with endothelin or norepinephrine, suggesting that the renal microvasculature can produce EDNO. Furthermore, this locally produced EDNO may be an important modulator of the vascular response to angiotensin II and endothelin (23,32).…”
Section: Discussionmentioning
confidence: 61%
“…A similar pressure-flow relation would have been expected as it would be induced by ACh that dilates both afferent and efferent arterioles (14,16,17). Renal vasodi lation induced by ACh might be a maximum, since other vasodilators such as bradykinin and prostaglandin E2 could not ailate the renal blood vessels to a greater extent than the dilation that would occur with ACh (23)(24)(25).…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, if a vasodilator increases RBF at reduced RPP, its site of action is presumably the efferent arteriole. Based on the above argument, pressure-RBF and pressure-GFR relations were obtained during infusion of adenosine and glucagon, or acetylcholine (ACh) which dilates both the afferent and the efferent arterioles (14,16,17). In addition, the effects of adenosine in combination with glucagon and the effects of ACh on pressure RBF and pressure-GFR relations were com pared.…”
mentioning
confidence: 99%